Properties of particleboard produced from admixture of rubberwood and Mahang species - Loh, Yang Way; H'ng, Paik San; Lee, Seng Hua; Lum, Wei Chen; Tan, Chun Knee (Knowledgia Review, Malaysia, 2010)
Particleboard is one of the major timber products exported from Peninsular Malaysia. Apparently, the increasing price and lack of supply of rubberwood has forced the particleboard manufacturers to look for new alternative raw material to produce particleboard. Hence, the production of particleboard through mixture of fast-growing wood species will be a good solution to the depleting wood supply issue. The objective of this study was to investigate the physical and mechanical properties of particleboard produced from admixtures of rubberwood and Mahang at different proportion levels and the properties were evaluated based on the Japanese Industrial Standard for particleboard (JIS A 5908-1994). The physical and mechanical data presented here, were analyzed using Analysis of Variance (ANOVA) and Least Significant Difference (LSD), to determine the significant differences of the variables. From the study, an increase in density resulted in increase of thickness swelling of particleboard. In addition, the water absorption for particleboard with density 500 kg m-3 was higher. For bending properties, admixture particleboard of rubberwood and Mahang had significantly lower wet and dry bending property. In terms of internal bond strength, decrease in rubberwood proportion resulted in decrease in the internal bonding strength of the particleboard.